2008
DOI: 10.1039/b717219b
|View full text |Cite
|
Sign up to set email alerts
|

Phosphazene vs.diazaphospholene PN-bond cleavage in spirocyclic cyclodiphosphazenes

Abstract: Thermolysis of 2-azido-1,3,2-diazaphospholenes offers access to novel and rare spirocyclic cyclodiphosphazenes. The spectroscopic data and X-ray structure of one representative of the 2-azido-1,3,2-diazaphospholenes reveals an ionic bonding situation explaining sufficiently its rather high thermal stability. The cyclodiphosphazenes were characterised by NMR, mass spectrometry, and X-ray diffractometry. The results of ESI-FT-ICR studies demonstrate the potential of these compounds to undergo reductive eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…1,3,2-Diazaphospholes, NHP, and 1,3,2-diazaphospholenium cations were also reported to react with a -diimines or a -diketones via [1 + 4] cycloaddition to give appropriate spirocyclic phosphorane derivatives [27,37,38,72,80] . Thermolysis of P-azido-NHPs was reported to proceed via cleavage of dinitrogen to produce rather stable cyclodiphosphazenes which were further found to be capable of undergoing mono-or diprotonation at the imino-nitrogen atoms [83] . ESI-FT-ICR mass spectrometry reveals that the cations upon collision induced activation undergo interesting fragmentation processes leading to cleavage of either four-or five-membered rings that are presumably best described as [2 + 2] or [1 + 4] retro-cycloadditions.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…1,3,2-Diazaphospholes, NHP, and 1,3,2-diazaphospholenium cations were also reported to react with a -diimines or a -diketones via [1 + 4] cycloaddition to give appropriate spirocyclic phosphorane derivatives [27,37,38,72,80] . Thermolysis of P-azido-NHPs was reported to proceed via cleavage of dinitrogen to produce rather stable cyclodiphosphazenes which were further found to be capable of undergoing mono-or diprotonation at the imino-nitrogen atoms [83] . ESI-FT-ICR mass spectrometry reveals that the cations upon collision induced activation undergo interesting fragmentation processes leading to cleavage of either four-or five-membered rings that are presumably best described as [2 + 2] or [1 + 4] retro-cycloadditions.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Hence, in all the above cases, larger macrocycles are anticipated as the sole product obtained (Scheme , method A). While species containing NH bridges within the P 2 N 2 ring have been previously described, they are rare and require the presence of tetracoordinate phosphorus atoms. Unfortunately, attempts to synthesize species of the type [(μ-N t Bu)­(μ-NH)­(PNH 2 ) 2 ] or [(μ-N t Bu)­(μ-NH)­(PCl) 2 ] were unsuccessful.…”
Section: Resultsmentioning
confidence: 99%
“…A search of the Cambridge Structural Database (Groom et al, 2016) indicated that no other 2-azido-1,3,2-(diarylamino)phospholidine derivatives have been structurally characterized. Some structurally similar compounds were identified, however, namely 2-azido-1,3-bis(2,6-diisopropyllphenyl)-1,3,2-diazaphospholene (CSD refcode CILBAC; Gediga et al, 2014) and its corresponding 2,6-dimethylphenyl derivative (GOFHAL; Burck et al, 2008). Acyclic derivatives featuring bis(diisopropylamino) (PIJZAJ; Englert et al, 1993) and bis(dicylohexylamino) (ZABCEK; Cowley et al, 1995) ligands are known, and also 1-azido-N,N 0 -bis(2,4,6-tri-tert-butylphenyl)phosphinediamine (YABVUV; Nieger et al, 2016).…”
Section: Database Surveymentioning
confidence: 99%